In the search for integrative biomarker of resilience to psychological stress. (March 2017) - Walker, Frederick R.; Pfingst, Kane; Carnevali, Luca; Sgoifo, Andrea; Nalivaiko, Eugene
Highlights: Resilience is assessed by psychometric instruments susceptible to self-report bias. We focus on physiological, neurochemical and immune markers of resilience. None of proposed biomarkers of resilience has sufficient discriminative power. The way to overcome this problem is to develop integrative measure. Most promising candidate markers for such integrative measure are proposed. Abstract: Psychological resilience can be defined as individual's ability to withstand and adapt to adverse and traumatic events. Resilience is traditionally assessed by subjective reports, a method that is susceptible to self-report bias. An ideal solution to this challenge is the introduction of standardised and validated physiological and/or biological predictors of resilience. We provide a summary of the major concepts in the field of resilience followed by a detailed critical review of the literature around physiological, neurochemical and immune markers of resilience. We conclude that in future experimental protocols, biological markers of resilience should be assesses both during baseline and during laboratory stressors. In the former case the most promising candidates are represented by heart rate variability and by in vitro immune cells assay; in the latter case—by startle responses (especially their habituation) during stress challenge and by cardiovascular recovery after stress, and by cortisol, DHEA and cytokine responses. Importantly, they should be used in combination to enhance predictive power.